Judicial review of the Tribunal for Consumer Claims' awards: a justice for whom? - Amin, Naemah (2011)
The establishment of the Tribunal for Consumer Claims (hereinafter referred to as “the TCC”) in 1999 may be considered as a major landmark in the development of consumer protection law in Malaysia. The TCC has received considerably good response from the public and the number of claims filed by consumers has risen substantially over the years. Nevertheless, in the course of offering an informal, faster and cheaper procedure to consumers, the TCC has to face with few challenges and one of the major challenges is judicial review. Just like other inferior courts or quasi-judicial bodies, the awards of the TCC may be subject to judicial review on questions of law. This procedure has been used by traders who are backed by huge financial resources and legal experts to challenge the Tribunal’s findings. On the other hand consumers who are dragged into the process may not be able to defend themselves without assistance from lawyers or consumer associations. For the same reason judicial review will not be used by consumers although there are instances where the Tribunal's awards were not in their favour. This paper aims to examine the judicial review of the TCC’s awards and its impact on consumers and the TCC’s reputation as an effective consumer redress mechanism.